LOGIT MODELS FOR PREDICTING BANKRUPTCY - Vlaović Begović, Sanja (International Journal of Economic Practice and Policy, 2018)
Going into bankruptcy represents main driver of company credit risk, because of which the monitoring of doing business is considered justified. Models that forecast company’s going into bankruptcy are efficient tool with whose application risk of doing business can be reduced. In the paper, the first models built on the foundations of logistic regression are presented. These models also have the biggest application in practice. Advantages and disadvantages of logit model for forecasting of bankruptcy are highlighted. Short display of logit model is incurred for concrete markets with special characteristics among which is market of Republic of Serbia too.